Extraction of oil from tiger nut (Cyperus esculentus L.) with supercritical carbon dioxide (SC-CO2). - Olusegun, Lasekan; Mohammed, Abdulkarim Sabo (Elsevier, 2012)
Supercritical carbon dioxide (SC-CO2) was used to extract oil from tiger nuts and the physicochemical properties and the impact of extraction conditions [i.e., temperature (40 °C–80 °C), pressure (20–40 MPa) and time (60–360 min)] on the oil yield were studied. The response surface analysis results revealed that the oil yield was significantly (P < 0.05) influenced by the main effect of the extraction pressure, extraction time and their quadratic effects respectively. However, the interaction between the extraction temperature and time had no significant (P > 0.05) effect on the oil yield. The highest oil yield was 26.28 g/100 g sample after 210 min of extraction time at 30.25 MPa and 60 °C respectively. The fatty acid composition of oils obtained by SC-CO2 and Soxhlet showed marked variation. Also, the fatty acid composition varied depending on the operating conditions. The viscosity of the oil decreased with the increase in temperature.